The effect of referee knowledge, leadership style and confidence on the performance of hockey referee - Mochamad Egi Margiyan; Sri Nuraini; Hernawan (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
Purpose of this research is to examine effect of refereeing knowledge with the performance of hockey referees, the influence of the hockey referee's leadership style in his performance in leading a match, the influence of referee's confidence and performance of hockey referee, the influence of refereeing knowledge on performance of referee through self-confidence, the influence of the referee's leadership style on the performance of hockey referee through self-confidence. The method used in this research is this research was carried out with an associative quantitative approach with surveys and tests and this study used the path analysis method which was carried out on 50 samples of hockey referees. Data analysis technique was carried out through two stages of analysis, namely descriptive and inferential data analysis. The first is descriptive data analysis, which is carried out to analyze the collected data in order to obtain a description of the distribution of characteristics of values ​​of each the variables studied. The results showed that direct effect of variable X1 on Y: 6.55%, Variable X2 on Y: 6.60%, Variable X1 on X3: 7,1%, Variable X2 on X3: 15.6 %, Variable X1 to Y through X3: 11.44%, Variable X2 to Y through X3: 14.40%.